2019
DOI: 10.1007/s40071-019-0216-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary exposure to melamine and cyanuric acid induced growth reduction, oxidative stress and pathological changes of hepatopancreas in Pacific white shrimp

Abstract: This study examined the effects of dietary melamine (MEL) and cyanuric acid (CYA) singly and in combination on growth, nutrient utilization, immunological responses, oxidative stress, and histological changes in Pacific white shrimp. Seven experimental isonitrogenous (35%) and isolipidic (8%) diets were formulated, namely diet 1 (a control diet without MEL and CYA); diets 2-5 (with MEL and CYA at 2.5 ? 2.5, 5 ? 5, 7.5 ? 7.5 and 10 ? 10 g kg -1 diet); diet 6 (with only MEL at 10 g kg -1 diet) and diet 7 (with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…In the present study, dietary uptake of MEL and MEF caused a significant reduction in body biomass of the exposed groups and may suggest underutilization of MEL/MEF contaminated diets. The findings of the present study validate the reports of previous studies, which emphasized the toxicity of MEL, as it caused significant reduction in growth of white shrimp (Nuntapong et al, 2019), red tilapia (Phromkunthong et al, 2013) and Asian sea bass (Phromkunthong et al, 2015). On the contrary, Samranrat et al (2011) reported no significant decrease in the growth of black Tiger shrimp treated with MEL doses ranging from 0.005 to 5.0 g Kg −1 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the present study, dietary uptake of MEL and MEF caused a significant reduction in body biomass of the exposed groups and may suggest underutilization of MEL/MEF contaminated diets. The findings of the present study validate the reports of previous studies, which emphasized the toxicity of MEL, as it caused significant reduction in growth of white shrimp (Nuntapong et al, 2019), red tilapia (Phromkunthong et al, 2013) and Asian sea bass (Phromkunthong et al, 2015). On the contrary, Samranrat et al (2011) reported no significant decrease in the growth of black Tiger shrimp treated with MEL doses ranging from 0.005 to 5.0 g Kg −1 ).…”
Section: Discussionsupporting
confidence: 91%
“…The liver is an essential organ for the detoxification of chemicals and is sensitive to stress responses (Yu et al, 2016). The result of this study consolidates the finding of Nuntapong et al (2019), who noted significant decreases in SOD, GPx and CAT activities in hepatopancreas of pacific white shrimp treated with 10 g Kg −1 MEL contaminated diet. Phromkunthong et al (2015) emphasized the toxicity of MEL following its inhibitory effect on GPx and CAT activities in the liver and kidney of Asian sea bass.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations